Teachers sourcebook for extensive reading - Jacobs, George M.; Farrell, Thomas S. C. (Emerald Publishing Limited : Information Age Publishing, 2012)
The best way for students to learn to read and to come to love reading is - surprise, surprise - by reading in quantity. Unfortunately, many of today's students read far too little. This lack of time spent reading is particularly unfortunate, as reading constitutes a bedrock skill, essential in all subject areas. Thus, we teachers need to devote curriculum time to not only teaching students how to read but also to encouraging them to read extensively. This is what Extensive Reading is all about.Teachers Sourcebook for Extensive Reading provides hundreds of teacher tested ideas on how to do Extensive Reading. The book begins with an introduction to 'the what' and 'the why' of Extensive Reading. Thereafter, the book consists of three parts. Part 1 discusses finding materials for Extensive Reading. Part 2 offers ideas for motivating students to read and for activities that students might do after they read or while they are reading, including cooperative learning activities. Part 3 looks at how teachers can serve as advocates for Extensive Reading.Among the book's distinctive features are breaks for reflection, first person accounts from teachers, and ideas for doing Action Research and other forms of teacher investigation and research on Extensive Reading. We hope that you will find the Teachers Sourcebook for Extensive Reading to be a practical book, but also informed by theory and researh. We also hope this book will make a difference for your students in their test scores and, even more, in their attitude toward reading, now and in the future.
Keywords: Reading.; Individualized reading instruction.; Children -- Books and reading.; Motivation in education.; Education -- Educational Policy & Reform -- General.; Educational strategies and policy.; elektronické knihy; electronic books